Generation of two heterozygous GAA mutation-carrying human induced pluripotent stem cell lines (XACHi005-A, XACHi006-A) from parents of an infant with Pompe disease - Wenjun Huang; Yafei Zhou; Jie Wang; Congshan Jiang; Yanmin Zhang; Rui Zhou (Stem Cell Research, 2022)
Pompe disease results from GAA mutations that leads to lysosomal glycogen accumulation and cardiac and skeletal muscle pathology. We have previously generated an infantile-onset Pompe disease patient-derived human-induced pluripotent stem cells (iPSCs) line carrying compound GAA mutations (R608X and E888X). Using his parents’ peripheral blood mononuclear cells (PBMCs), we here generated two iPSCs lines which carry mutations of R608X E888X respectively. Both lines show typical cell morphology, high expressed pluripotent and self-renewal markers, normal karyotype, and trilineage differentiation potential. These two lines are valuable re-sources for studying the pathological mechanisms of GAA mutation-caused Pompe disease.